2003
DOI: 10.1249/00149619-200302000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Pathophysiology of Minor Traumatic Brain Injury

Abstract: This review article presents evidence from the current literature on the epidemiology and pathophysiology of concussion. The recent epidemiologic data for a variety of sports are presented relevant to the general population, and professional, college, and high school athletics. The evidence for the pathophysiology of head injury is presented using a mixture of current animal and human studies. A brief discussion on the benefits and limitations of the evidence is offered for the both the epidemiology and pathop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 46 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…Many physiological consequences of mTBI normalize by 2 weeks after the initial injury (Giza & Hovda, 2001;Grindel, 2003), leading Broglio and Puetz (2008) to assess recovery from sportsrelated mTBI across a 14-day postinjury timeframe. These authors did not find time since injury uniquely predictive of effect size at initial assessment; however, restricted range of time since injury and colinearity of this variable with other predictors in their Comparatively, a more recent meta-analysis (Dougan et al, 2013) identified a slight increase in effect size from 24 hr postinjury (d ϭ .38) to 1-10 days postinjury (d ϭ .54), but this trend reversed (i.e., d ϭ .90 at 24 hr; d ϭ .41 at 1-10 days) when including only effect sizes from more rigorous designs (i.e., those involving both selfcontrol and independent control group comparisons).…”
Section: Time Since Injurymentioning
confidence: 99%
“…Many physiological consequences of mTBI normalize by 2 weeks after the initial injury (Giza & Hovda, 2001;Grindel, 2003), leading Broglio and Puetz (2008) to assess recovery from sportsrelated mTBI across a 14-day postinjury timeframe. These authors did not find time since injury uniquely predictive of effect size at initial assessment; however, restricted range of time since injury and colinearity of this variable with other predictors in their Comparatively, a more recent meta-analysis (Dougan et al, 2013) identified a slight increase in effect size from 24 hr postinjury (d ϭ .38) to 1-10 days postinjury (d ϭ .54), but this trend reversed (i.e., d ϭ .90 at 24 hr; d ϭ .41 at 1-10 days) when including only effect sizes from more rigorous designs (i.e., those involving both selfcontrol and independent control group comparisons).…”
Section: Time Since Injurymentioning
confidence: 99%
“…Evidence also shows that concussions are under-reported in youth ice hockey [13 ]. Soccer, wrestling, basketball, field hockey and lacrosse are similarly associated with a high number of concussions [14,15].…”
Section: Epidemiologymentioning
confidence: 99%
“…3,4 A thorough understanding of the epidemiology of head injuries enables coaches and medical staff to review the adequacy of their injury prevention and rehabilitation strategies and inform the planning of training programs. 5 With almost 200 countries affiliated with the International Rugby Board (iRB), rugby union is the world's most popular collision team sport.…”
Section: Introductionmentioning
confidence: 99%